Understanding fundamentals of hepatocellular carcinoma to design next-generation chitosan nano-formulations: Beyond chemotherapy stride - Jaiswal, Neha; Chaudhari, Ravindra D.; Chaudhari, Bhushan P. (Journal of Drug Delivery Science and Technology, 2020)
Hepatocellular carcinoma (HCC) is the deadliest form of liver cancer. Clinically, the main strategies currently being used for the treatment of HCC are surgery, radiotherapy and chemotherapy. Conventional chemotherapy has major drawbacks such as poor bioavailability, high-dose requirements, adverse side effects, low therapeutic indices, and non-specific drug targeting. Therefore, targeted drug delivery systems are fast becoming new tools for the selective killing of cancer cells. Chitosan (CS) is a biodegradable, biocompatible, cationic and natural biopolymer that also exhibits anti-cancer property which is now being explored as a promising candidate for targeted drug delivery. This review outlines an overview of the causative agents, microenvironment, pathophysiology, surface-biomarkers and physiological barriers of HCC. Then, the cellular internalization pathways of nanomedicine and the important physicochemical properties of delivery agents are discussed. The benefits of targeted therapy over conventional therapy with regard to HCC are also discussed. The main objective of this review was to summarize the current knowledge in the field of chitosan-based drug delivery for the management of HCC along with its limitations in a comprehensive and systematic way. This review attempts to provide a holistic roadmap for designing the next-generation chitosan-based drug delivery systems for HCC management.
Keywords: chitosan nanoparticles; Hepatocellular carcinoma; Pathophysiology; Surface biomarkers; Targeted Drug Delivery; Tumor microenvironment

Biosynthesis of gold nanoparticles by Penicillium rubens and catalytic detoxification of ochratoxin A and organic dye pollutants - Bhandari, Yogesh; Varma, Sanjana; Sawant, Amol; Beemagani, Sreelatha; Jaiswal, Neha; Chaudhari, Bhushan P.; Vamkudoth, Koteswara Rao (International Microbiology, 2023)
The environmental pollution caused by chemical dyes is a growing concern nowadays. Limitations of traditional methods opened the route for nanotechnology; owing to the versatile properties of nanomaterials, gold nanoparticles (AuNPs) became a potential strategy for different applications. In the present study, biosynthesis of gold nanoparticles (BioAuNPs) was carried out by reacting chloroauric acid (HAuCl4) with cell-free filtrate of Penicillium rubens sp. nov. NCIM 1937. The AuNPs were then characterized by UV-visible spectroscopy, HR-TEM, FTIR, and DLS analysis to further examine their efficacious biosynthesis and morphological properties including size, shape, and stability. The biogenic AuNPs are polydisperse in nature, with a mean size of 14.92 +/- 5 nm. These AuNPs exhibited promising antimicrobial activity against Escherichia coli NCIM-2065, Bacillus subtilis NCIM-2010, and Penicillium verrucosum MTCC 4935. In vitro quantitative HPLC results revealed that BioAuNPs significantly inhibited the biosynthesis of ochratoxin A (OTA). Microbial fuel cells (MFCs) are intriguing for power generation and wastewater treatment since they can directly transform chemical energy stored in organic matter to electricity by extracellular electron transfer (EET) via membrane proteins. AuNPs also showed excellent potential for dye degradation of organic pollutants, viz., methylene blue (MB), phenol red (PR), bromothymol blue (BTB), Congo red (CR), and 4-nitrophenol (4-NP). All dye removal efficiencies were estimated and fitted to pseudo-first-order processes using kinetic rate constants (Ka).The present study reveals a simple, original, and eco-friendly method for the synthesis of multifunctional biogenic AuNPs that could be effective in OTA detoxification in food products and organic pollutant removal during wastewater treatment for a sustainable environment.
Keywords: Catalytic organic dye degradation; gold nanoparticles; Ochratoxin A; Penicillium rubens; Penicillium verrucosum

Chitosan nanoparticles for single and combinatorial delivery of 5-fluorouracil and ursolic acid for hepatocellular carcinoma - Jaiswal, Neha; Pawar, Anil T.; Chaudhari, Bhushan P. (Emergent Materials, 2024)
Hepatocellular carcinoma (HCC) remains a significant global health challenge with limited therapeutic options. Chemotherapy has major limitations, leading to a paradigm shift towards nanomedicines. In this study, we aimed to synthesize single and dual drug-loaded chitosan nanoparticles (CSNPs) containing 5-fluorouracil (5-FU) and ursolic acid (UA) for spatial and controlled delivery against HCC. We synthesized CSNPs by a modified bottom-up ionic gelation method and optimized various parameters to formulate particles with smaller sizes, uniform size distribution, and high surface charge for intra-arterial infusion for HCC. The characterization techniques confirmed a monodisperse population of smaller sized particles with average sizes, as determined from transmission electron microscopy (TEM), as 45.25 ± 11.58, 105.66 ± 10.96, 176 ± 16.46, and 220 ± 21.37 nm for CSNPs, 5-FU-CSNPs, UA-CSNPs and 5FU + UA-CSNPs respectively. These formulations exhibited excellent encapsulation of the drugs, with an initial pH-dependent rapid release of 5-FU followed by a subsequent slower and sustained release, while showing pH-dependent slow and controlled release of UA. The in vitro cell viability assay established the highest anticancer potential for 5FU + UA-CSNPs, followed by 5-FU-CSNPs and UA-CSNPs, and the lowest for plain drugs in the Hep3B cell line. An increased uptake of both the drugs in CSNPs substantiated the supremacy of these formulations over the plain drugs as drug delivery agents. These findings suggest that 5FU + UA-CSNPs, a novel formulation, works as a potent therapeutic agent against HCC, supporting our hypothesis of co-loading 5-FU and UA in CSNPs can effectively manage HCC, with particle attributes fit for administration via intra-arterial infusion.